2015
DOI: 10.11622/smedj.2015072
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected colorectal carcinoma on routine abdominopelvic computed tomography

Abstract: Colorectal carcinoma is a common lethal disease with signs and symptoms that may be nonspecific. Computed tomography (CT) of the abdomen and pelvis with or without contrast is frequently performed for various general abdominal complaints, but unlike CT colonography, the large bowel may not be optimally prepared for evaluation. As such, careful and diligent assessment of the non-prepared colon in all CT images of the abdomen and pelvis is important, as it ensures that incidental colorectal malignancy is not mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…From 2015 to 2020, an average of 92.5% of CRC was diagnosed in those over the age of 50 years and the absolute incidence rates of EOCRC are a small fraction of those seen in older patients (Table 1). It is also worth considering that for patients over the age of 80 years, the increasing incidence rates may be a result of increased detection, rather than a true increasing prevalence of disease, e.g., increasing incidental findings of CRC picked up on cross sectional imaging for another indication [58]. Whatever the cause, due to the rapidly aging population the volume of CRC diagnoses in patients over 80 years is set to increase dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…From 2015 to 2020, an average of 92.5% of CRC was diagnosed in those over the age of 50 years and the absolute incidence rates of EOCRC are a small fraction of those seen in older patients (Table 1). It is also worth considering that for patients over the age of 80 years, the increasing incidence rates may be a result of increased detection, rather than a true increasing prevalence of disease, e.g., increasing incidental findings of CRC picked up on cross sectional imaging for another indication [58]. Whatever the cause, due to the rapidly aging population the volume of CRC diagnoses in patients over 80 years is set to increase dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…The Danish screening program paper from 2015 revealed that the rate of incidentally detected malignant polyps was 2.3% [ 3 ]. It is also reported as an incidental finding in CT or PET scans being performed for other indications [ 2 ]. Incidental large bowel malignancy also has been noticed during surgery for other causes as in resected inguinal hernia sac, or during laparotomy for intestinal foreign body [ 10 ], and it was also detected in resected bowel after gunshot injuries [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidental colorectal carcinoma is defined as a clinically inapparent carcinoma of the large intestine diagnosed or discovered unexpectedly. It can be detected in imaging for other reasons [ 2 ], during colonoscopy bowel cancer screening [ 3 ], during surgical intervention for unrelated causes, as well as in autopsy. In this case, it was discovered during pathologic examination of a subtotal colectomy specimen removed for ischaemic colitis.…”
Section: Introductionmentioning
confidence: 99%
“…CT scan is actually a poor diagnostic tool for detection of colonic malignancies with only 70% sensitivity with an unprepared bowel and even less in the setting of acute appendicitis [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%